Effect of two natural rooting agents and a synthetic one on the propagation of blackberry (Rubus robustus C. Presl). - Miranda Barrios, Elizabeth Antonia (2022)
The blackberry is a crop that has become important for its commercial and nutritional value, this caused its cultivation increase areas discreetly. In this sense, the objective of the present investigation was to evaluate the effect of two natural rooting agents from young stems and leaves of willows and lentil radicles and synthetic rooting agent root-hor in the propagation of cuttings and rhizomes of blackberries (Rubus Fructicosus L. ninai) during October - December. A complete randomized design (DCA) with 24 treatments and 9 repetitions was conducted. Root length, neck diameter, number of shoots and plant size were evaluated. The best results were observed in the rhizomes, where treatment T03 stood out, followed by T9, T20, T17, T19, T21, T16 and T18; Regarding the cuttings, only the T6 treatment had root. It is concluded that the best results are found when blackberry is propagated through rhizomes and minimal to no use of hormones, where treatment T03 and T9 are superior.